2017
DOI: 10.1891/0886-6708.vv-d-16-00040
|View full text |Cite
|
Sign up to set email alerts
|

Tweets, Gangs, and Guns: A Snapshot of Gang Communications in Detroit

Abstract: The aim of the present study is to determine the frequency of violent and criminal Twitter communications among gang affiliated individuals in Detroit, Michigan. We analyzed 8.5 million Detroit gang members’ tweets from January 2013 to March 2014 to assess whether they contained Internet banging-related keywords. We found that 4.7% of gang affiliated user tweets consisted of terms related to violence and crime. Violence and crime-related communications fell into four main categories: (1) Beefing (267,221 tweet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…One individual can reach hundreds or thousands of others in a matter of seconds no matter their location, communicating threats constantly throughout time and space. Social media utilization for threats is not restricted to keywords but often include mentions of offline events, people, local institutions, and situations that may inform how and why a post is perceived as threatening (Patton et al 2017c). In this sense, one social media spark can escalate communication between rival groups who compete for reputation, territory, markets, and the upper hand in violent encounters.…”
Section: Gang-involved Youth Use Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…One individual can reach hundreds or thousands of others in a matter of seconds no matter their location, communicating threats constantly throughout time and space. Social media utilization for threats is not restricted to keywords but often include mentions of offline events, people, local institutions, and situations that may inform how and why a post is perceived as threatening (Patton et al 2017c). In this sense, one social media spark can escalate communication between rival groups who compete for reputation, territory, markets, and the upper hand in violent encounters.…”
Section: Gang-involved Youth Use Of Social Mediamentioning
confidence: 99%
“…Despite the important role social media plays in periodic surges and steady persistence of youth violence, little extant research attempts to understand how youth perceive, categorize, and react to aggressive and potentially threatening social media posts. Therefore, a crucial challenge for researchers and practitioners working with gang-involved youth is to determine the conditions where social media use can lead the youth to become involved in violence, either as victims or perpetrators (Patton et al 2017c). This article fills a significant gap by asking formerly gang-involved youth in Chicago to interpret communication on Twitter from two prominent crews on Chicago's South Side.…”
mentioning
confidence: 99%
“…Theories about identity predict that the degree to which a gang member cares about peers or authority figures is contingent on the prominence and salience of his or her gang identity . Scholars have identified numerous examples of gang identity performances that highlight violence even when this may lead to negative attention from relatives, school administration, and law enforcement (e.g., Lauger & Densley, ; Patton, Lane, Leonard, Macbeth, & Smith Lee, ; Patton, Patel, et al, ; Storrod & Densley, ). Gang members post threatening messages on Twitter or directly threaten other gang in rap lyrics on YouTube (Lauger & Densley, ; Patton, Lane, et al, ).…”
Section: Gangs and Performancementioning
confidence: 99%
“…As grief turns to anger, their posts turn to retribution and ultimately to plans for revenge (Patton et al, 2018b). Research in this space has shown that online posts often affect life in the real world (Moule et al, 2013;Patton et al, 2013;Pyrooz et al, 2015;Patton et al, , 2017a. In some communities, violence outreach workers manually scour online spaces to identify such possibilities and intervene to diffuse situations.…”
Section: Introductionmentioning
confidence: 99%